Present Value and Gossen's First Law - A Case Study - Piasecki , Krzysztof (Studia Oeconomica Posnaniensia, 2015)
The main aim of this study was to verify the existence of an economically justified non-additive present value function. The study assumed the validity of the principle of the diminishing marginal utility of wealth. Two types of constant risk aversion coefficients were considered: the absolute coefficient and the relative coefficient. As a result, two different models for discounting functions were obtained. The formal influence of behavioural factors on the discount rate has been demonstrated.